Dataset of digital literacy of university students in Indonesia - Ermida Simanjuntak; Happy Cahaya Mulya; Agustina Engry; Ilham Nur Alfian (Data in Brief)
Digital literacy entails the ability to collect information, comprehend text on multimedia platforms, critically evaluate information, and communicate that information collaboratively. These skills are essential for university students to interact appropriately in cyberspace. This dataset aims to provide a comprehensive overview of digital literacy skills among university students in Indonesia. It comprises responses from 2921 university students (805 males and 2116 females) from various regions across the country. Data were measured using a digital literacy scale consisting of six subscales: technological skill, personal security skill, critical skill, device security skill, informational skill, and communication skill. This dataset plays an important role in describing the prevalent digital literacy competencies among Indonesian university students. It can contribute valuable information for the development of digital literacy programs to enhance these skills among Indonesian university students. Furthermore, this dataset holds academic significance for researchers interested in conducting cross-cultural comparisons of digital literacy trends among university students in different global contexts.